Zależność zakresu fuzji od wybranych funkcji układu wzrokowego. Część I: badania fuzji konwergencyjnej i dywergencyjnej - Adamek, Bogdan; Karczewicz, Danuta (Klinika Oczna / Acta Ophthalmologica Polonica, 2006)
After examined 132 patients, the authors selected 90 patients with correct visual acuity of both eyes, correct range of eyeballs’ mobility, parallel setting of the eyeballs, no difference in refraction between both eyes and with muscular balance. These 90 patients were divided into 3 groups: children between 8 and 10 years old, teenagers between 11 and 20 years old and adult people between 21 and 40. All the groups were subject to the main examination of the study carried out by means of prism bar and synoptophore for each of the eye separately. The results were compared in order to define the difference in the range of fusion between both eyes. The study involved an examination of horizontal range of convergent and divergent synoptophoric fusion as well as that of free space for near and for far. A statistically significant difference between both eyes was observed in range of synoptophoric, for near and for far convergent fusion. The difference was confirmed in an average of 35.6% of patients for convergent fusion for near, in 34.4% of patients for convergent fusion for far, and in 65.6% of patients for synoptophoric convergent fusion. The mean difference between the eyes in the range of fusion was: 4.6° for convergent fusion for near, 3.9° for convergent fusion for far and 6.4° for synoptophoric convergent fusion. No significant differences between both eyeballs were detected in the range of divergent fusion. The authors suggested calling the phenomenon connected with the difference between both eyeballs in convergent fusion the following term: “visual unevenness of the range of convergent fusion”.